2023
DOI: 10.1109/tie.2022.3165250
|View full text |Cite
|
Sign up to set email alerts
|

Open-Circuit Radial Stray Magnetic Flux Density Based Noninvasive Diagnosis for Mixed Eccentricity Parameters of Interior Permanent Magnet Synchronous Motors in Electric Vehicles

Abstract: By measuring the open-circuit radial stray magnetic flux density (RSMFD) of three spatial points, a novel diagnostic method for the eccentricity of interior permanent magnetic motors (IPMSMs) in electric vehicles (EVs) is proposed. Outperforming traditional methods, the proposed method can non-invasively diagnose not only the severities of static eccentricity (SE), dynamic eccentricity (DE), and mixed eccentricity (ME), but also the eccentricity location. In this paper, diagnosis results are described through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Besides, Bruzzese C. et al found that the amplitude of the second harmonic ripple in rotor current is proportional to the degree of the SAGE fault [7], and the first and third harmonic amplitudes of the electromotive force increased significantly under the SAGE fault [8]. Based on the electromechanical characteristics, diagnosis and monitoring of SAGE faults are carried out [9][10][11][12][13][14]. In addition, the magnetic flux and the shaft voltage are common and useful indicators to measure air-gap eccentricity.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, Bruzzese C. et al found that the amplitude of the second harmonic ripple in rotor current is proportional to the degree of the SAGE fault [7], and the first and third harmonic amplitudes of the electromotive force increased significantly under the SAGE fault [8]. Based on the electromechanical characteristics, diagnosis and monitoring of SAGE faults are carried out [9][10][11][12][13][14]. In addition, the magnetic flux and the shaft voltage are common and useful indicators to measure air-gap eccentricity.…”
Section: Introductionmentioning
confidence: 99%
“…In order to achieve efficient control of PMSMs in these fields, scholars have designed many advanced controllers, such as field-oriented control (FOC) [5] and direct torque control (DTC) [6]. The accurate model and parameters of the PMSM are crucial for the performance release of these controls and the design of fault diagnosis systems [7].…”
Section: Introductionmentioning
confidence: 99%
“…Presently, the air-gap model for ME is usually written as the sum of SE and DE. Based on this model, the influence of ME on the radial force of PM motors [14], the dynamical model of induction motors under ME [15] and the influence of ME on air-gap flux density of PM motors [16] were analyzed. Yet the application of this model relies on a complex analysis process, where the influence of ME on cogging torque harmonic components could not be comprehensively explained.…”
mentioning
confidence: 99%